2020
DOI: 10.3399/bjgpopen20x101124
|View full text |Cite
|
Sign up to set email alerts
|

GP involvement after a cancer diagnosis; patients’ call to improve decision support

Abstract: Background Shared decision making (SDM) is considered important to realise personalised cancer care. Increased general practitioner (GP) involvement after a diagnosis is advocated to improve SDM. Aim To explore if cancer patients are in need of GP involvement in cancer care in general and in SDM, and whether GP involvement occurred. Design and Setting An online national survey distributed by the Dutch Federation of Cancer Patient Organisation (NFK) in May 2019. Methods The survey was sent to (former) cancer pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…In line with our findings, other literature reports that GPs' involvement in caring for people with advanced cancer is common (31)(32)(33)(34) and perceived as valuable (23,27,37). Descriptions of involvement include practices that may support SDM, for example by clarifying diagnoses and adverse treatment effects and acting as an intermediary between patients and medical specialists (25,35,41).…”
Section: Comparison With Existing Literaturesupporting
confidence: 88%
See 1 more Smart Citation
“…In line with our findings, other literature reports that GPs' involvement in caring for people with advanced cancer is common (31)(32)(33)(34) and perceived as valuable (23,27,37). Descriptions of involvement include practices that may support SDM, for example by clarifying diagnoses and adverse treatment effects and acting as an intermediary between patients and medical specialists (25,35,41).…”
Section: Comparison With Existing Literaturesupporting
confidence: 88%
“…They are accustomed to a holistic approach to health problems and, generally, receive training in effective communication (24). A recent survey among cancer patients showed that the majority appreciates involvement of the GP in cancer care after diagnosis (27). Moreover, GPs' involvement may lead to higher patient satisfaction, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that not all patients can be recognised as having a limited life expectancy, and that, for example, a DNR‐order is not always related to a limited life expectancy. However, adequate information exchange is also important for patients with a limited life expectancy of more than 3 months, because it can contribute to high‐quality palliative care (Noteboom et al, 2021; Stegmann et al, 2020). In our study for one in four patients, their limited life expectancy was documented in the medical record but lacking in the discharge letter.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge about the patient's medical condition and about decisions and agreements regarding medical treatment can support the general practitioner in addressing the patient's care needs (Haggerty et al, 2003). Other studies found that the majority of all patients with cancer would prefer to talk with their general practitioner about end‐of‐life issues and also value support from their general practitioner in making treatment decisions (Noteboom et al, 2021). Stegmann et al found that patients with incurable cancer preferred their healthcare professional to take the initiative for this conversation (Stegmann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is often unclear whether the responsibility for care of those living with and beyond cancer lies with primary, secondary or tertiary care 21 . A large cross-sectional survey found that 59% of patients with a previous cancer expressed a need for increased GP involvement in cancer care, with the majority also stating that GPs are well-placed to listen to patients' concerns and discuss their priorities in order to support shared decision-making 22 . Patients who perceive the GP to be informed about their cancer were more satisfied with treatment decisions 23 , and those who speak with their GPs between diagnosis and commencement of treatment have improved satisfaction 24 .…”
Section: Introductionmentioning
confidence: 99%